Epidemiological investigation of an outbreak of viral hepatitis in a defence establishment - Mukhopadhyay, J. (International Journal Of Community Medicine And Public Health, 2017)
Background: An outbreak of viral hepatitis occurred in a defence establishment with 42 cases during November 10 to February 11. Methods: All suspected cases were clinically assessed according to standard clinical case description, investigated, admitted in hospital till recovery and thereafter sent on sick leave for complete recuperation. Epidemiological investigation included surveillance of data, initiation of epidemiological case sheets, sanitary inspection and environmental investigation of the affected area, bacteriological test of water samples and review of old relevant record. Results: Point source sewage contamination of water supply was detected at a particular block of a bachelor residential quarter. The outbreak was unimodal, localized, short lasting mostly involving young adults and responded once the control measures were adopted. Suspected water samples showed high coliform count when subjected to bacteriological test. Conclusions: The outbreak of viral hepatitis occurred due to sewage contamination of water supply. Alternate source of purified water supply, repair of leakages, change of water supply lines and water quality monitoring were recommended.